ISLAMIC POLITICAL CCOMMUNICATION IN MAINTAINING RELIGIOUS HARMONY AMONG THE PEOPLE IN TANA TORAJA - Firdaus Muhammad; Muhammad Al-Hashim Anshari (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
Islamic political communication highlights the social and political role of religious life so that it is not trapped in identity politics and conflict in the name of religion, so it is necessary to maintain religious harmony. The view is based on a process that aims to provide influence to achieve the social connectedness expected by each individual in society. Harmony is an attractive thing in a pluralistic society. A life of mutual acceptance, mutual respect, mutual assistance and mutual cooperation between religious followers is what everyone wants. The public in dynamic life sometimes causes conflict. Tana Toraja Regency is an area where the majority of the population is Christian, but the people live in harmony and are even far from conflict, all of this is supported by very strong family ties, shared traditions, ancestral ties and awareness of love for the land of birth. Apart from that, custom is also an important factor in creating harmony in the Tana Toraja community. Harmony in Tana Toraja society is not based on coercive methods but has existed for a long time. Social Communication is a communication activity with a direction and goal of achieving a condition of social integration.